Birth month distribution and anthropometric measures of U-15 national elite soccer players - Melo Altimari, J.; Bortolotti, H.; dos Santos-Junior, N.; Altimari, L. R.; de Moraes, A. C. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2018)
The aim of this study was to analyze the birth month distribution and anthropometric measurements of U-15 elite soccer players. The sample consisted of 400 athletes (15.4 ± 0.4 years, 171.0 ± 10.6 cm and 63.0 ± 8.8 kg) participants of the 11th edition of the Brazil U-15 Soccer Cup, who had their birth month information and height and body mass measures obtained from data available on the organization`s website. Athletes were separated according to the categorization of chronological age into four-month periods: 1st quarter (1st QDT), athletes born between January and April; 2nd quarter (2nd QDT), those born between May and August, and 3rd quarter (3rd QDT), those born between September and December. The non-parametric chi-square test (X2) was used to analyze the possible differences between observed and expected birth date distributions in the four-month periods. The significance level was P<0.05. The results show that the number of players born in 1st QDT was higher when compared to 2nd QDT and 3rd QDT (P<0.05), and higher when compared to 2nd QDT with 3rd QDT (P<0.05). For variables height and body mass, it was observed that players born in 1st QDT presented values significantly higher than those born in 2nd QDT and 3rd QDT (P<0.05). In the same way, players born in 2nd QDT presented higher values than those born in 3rd QDT (P<0.05).It could be concluded that the relative age effect exerts an influence on the selection of Brazilian U-15 soccer players because it is associated with differences in the anthropometric characteristics of these young players.